PENGARUH EXPERIENTIAL MARKETING TERHADAP WORD OF MOUTH DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING PADA CUSTOMER GRAB MATARAM - Fitria Ika Agustina; Eluiz Yansirus Saniyah (LPSDI Bina Patria, 2022)
This research is aimed to examining the effect of experiential marketing and word of mouth with satisfaction as an intervening variable on grab customers in the mataram city. the type of research conducted is associative kasuality. the sample design uses non probability sampling and accidental sampling technique is used to determine sampling with an unknown population. the sample taken was grab customers in the mataram city, which amounted to 100 samples. data analysis uses path analysis with the smartpls program. the results showed that experiential marketing had a positive and not significant effect on word of mouth, experiential marketing had a positive and significant effect on satisfaction, and satisfaction had a positive and not significant effect on word of mouth grab customers in mataram city. Then word of mouth is influenced by experiential marketing with satisfaction mediation. in general go- jek still needs to introduce its products to the community in the mataram city. by creating more localized advertisements, participating in local events, and improving driver services for customers in the mataram city.